1979
DOI: 10.1029/ja084ia09p05153
|View full text |Cite
|
Sign up to set email alerts
|

PC 4 giant pulsations in the morning sector

Abstract: Geomagnetic micropulsations in the Pc 4 frequency band which are highly monochromatic and have amplitude‐modulated wave forms have been termed ‘giant pulsations’ and have been observed to reach amplitudes of several tens of nanoteslas. In this paper, four such events are analyzed by using meridian line and two‐dimensional magnetometer networks. It is found that these pulsations are highly localized in latitude and have a large azimuthal wave number k⊥, although the large magnitude of k⊥ does not necessarily re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 25 publications
6
30
0
Order By: Relevance
“…These nearly monochromatic waves are usually observed during quite geomagnetic conditions, when the plasmapause lies somewhere at L ∼ 5.5 − 6, and giant pulsations (Pg) are recorded just there. Rostoker et al (1979) were the first to notice this. The assumption that Pg are resonator modes on the outer edge of the plasmapause is consistent with the strong localization of Pg across magnetic shells accompanied by a phase change by 180 degrees (Green, 1979;Rostoker et al, 1979;Glassmeier, 1980), and the amplitude distribution in L is described by the Gaussian function with the halfwidth of about 1 R E (Chisham et al, 1997), and this is indeed expected for the fundamental radial harmonic within the resonator on the outer edge of the plasmapause.…”
Section: On the Observation Of Toroidal And Poloidal Alfvén Waves In mentioning
confidence: 90%
“…These nearly monochromatic waves are usually observed during quite geomagnetic conditions, when the plasmapause lies somewhere at L ∼ 5.5 − 6, and giant pulsations (Pg) are recorded just there. Rostoker et al (1979) were the first to notice this. The assumption that Pg are resonator modes on the outer edge of the plasmapause is consistent with the strong localization of Pg across magnetic shells accompanied by a phase change by 180 degrees (Green, 1979;Rostoker et al, 1979;Glassmeier, 1980), and the amplitude distribution in L is described by the Gaussian function with the halfwidth of about 1 R E (Chisham et al, 1997), and this is indeed expected for the fundamental radial harmonic within the resonator on the outer edge of the plasmapause.…”
Section: On the Observation Of Toroidal And Poloidal Alfvén Waves In mentioning
confidence: 90%
“…However, Rostoker et al (1979) reported ground magnetometer observations of highly monochromatic Pc4 giant pulsations in the auroral zone that reoccurred on successive days during quiet geomagnetic conditions. They suggested that the Pc4 pulsations may be due to the occurrence of field line resonances at the plasmapause in the region where the electric field changes its azimuthal direction from westward to eastward.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterised by their large amplitudes, and their striking quasi-monochromatic wave form with periods of typically 100 s. Giant pulsations have been studied intensively in the past by e.g. Annexstad and Wilson (1968), Green (1979), Rostoker et al (1979), Glassmeier (1980), and more recently by Chisham and Orr (1991), Chisham et al (1992), Takahashi et al (1992), Chisham and Orr (1994), Chisham (1996), and Chisham et al (1997).…”
Section: Introductionmentioning
confidence: 99%